A cross‐sectional clinical study in women to investigate possible genotoxicity and hematological abnormalities related to the use of black cohosh botanical dietary supplements. (28th November 2022) - Smith‐Roe, Stephanie L.; Garantziotis, Stavros; Church, Rebecca L.; Bemis, Jeffrey C.; Torous, Dorothea K.; Shepard, Kim G.; Hobbs, Cheryl A.; Waidyanatha, Suramya; Mutlu, Esra; Shockley, Keith R.; Kissling, Grace E.; McBride, Sandra J.; et al.
Abstract: Black cohosh (BC; Actaea racemosa L.), a top‐selling botanical dietary supplement, is marketed to women primarily to ameliorate a variety of gynecological symptoms. Due to widespread usage, limited safety information, and sporadic reports of hepatotoxicity, the Division of the National Toxicology Program (DNTP) initially evaluated BC extract in female rats and mice. Following administration of up to 1000 mg/kg/day BC extract by gavage for 90 days, dose‐related increases in micronucleated peripheral blood erythrocytes were observed, along with a nonregenerative macrocytic anemia resembling megaloblastic anemia in humans. Because both micronuclei and megaloblastic anemia may signal disruption of folate metabolism, and inadequate folate levels in early pregnancy can adversely affect neurodevelopment, the DNTP conducted a pilot cross‐sectional study comparing erythrocyte micronucleus frequencies, folate and B12 levels, and a variety of hematological and clinical chemistry parameters between women who used BC and BC‐naïve women. Twenty‐three women were enrolled in the BC‐exposed group and 28 in the BC‐naïve group. Use of any brand of BC‐only supplement for at least 3 months was required for inclusion in the BC‐exposed group. Supplements were analyzed for chemical composition to allow cross‐product comparisons. All participants were healthy, with no known exposures (e.g., x‐rays, certain medications) that could influence study endpoints. Findings revealed no increased micronucleus frequencies and no hematological abnormalities in women who used BC supplements. Although reassuring, a larger, prospective study with fewer confounders (e.g., BC product diversity and duration of use) providing greater power to detect subtle effects would increase confidence in these findings.